KKN, SUPREMASI HUKUM DAN MORAL ISLAM - Dr. Djaenab Djaenab (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
Corruption is a misappropriation or embezzlement (state money / enterprise, etc.) for personal or other interests. While nepotism is a tendency to prioritize (benefit) relatives themselves, especially in terms of position, rank in the government environment, or the act of choosing relatives or relatives to hold the government. Factors that encourage the KKN, among others; 1) good opportunity, 2) Due to the general condition of economy and low government salary, 3) weakness of government administration, 4) The absence of assertiveness by those assigned to carry out law against perpetrators of KKN resulted in KKN become common phenomenon and the usual thing. The Role of Supremacy of Islamic Perspective Law anticipates KKN, among others; 1) Establish an independent alliance as an anti-corruption movement involving elements of society, students, NGOs and the press. 2) Students as academic people, who are the drivers of reform to not hesitate to go to the prosecutor's office to report the corruption case he found. 3) This movement must have a strong network to dismantle the case of KKN with a press that has an important role in this regard.